Symposium climaterio and menopause: Introduction - Saona Ugarte, Pedro (2015)
The advancement of science and technology has determined that the life expectancy of humans has increased significantly over the past 50 years. Currently, it is estimated that Peruvian women live on average to 74 years; and with the average age of menopause around age 47, this means that almost a third of his life will be exposed to physiological changes that begin in perimenopause and after menopause continue.